Coronary artery disease - Stewart, T.F. (British Homeopathic Journal, 1966)
This paper has discussed the diagnosis, age incidence, medicinal treatment and mortality of coronary artery disease. From the case records of forty patients admitted to the Glasgow Homœopathic Hospital with coronary disease it has extracted the individual symptoms on which homœopathic medicines were prescribed for individual patients. The main part of the discussion is on the homœopathic remedies used, the remedies are discussed in the order of frequency of use, but the incidents reported are selected for their individual interest.